Post-traumatic growth as experienced by family caregivers of cancer patients in Iran: a qualitative content analysis - Naeem Abdi; Marzieh Momennasab; Shahrzad Yektatalab; Azita Jaberi (BMC Palliative Care)
Abstract Background Growth is not a direct consequence of trauma, but rather a struggle against overwhelming and stifling conditions, from which post-traumatic growth is born. Since post-traumatic growth as a psychological construct, has emerged from research conducted across various cultural and social context, it seems necessary to study the perceptions and experiences of individuals in the culture and religion of each society. Thus, this qualitative content analysis study aimed to explore the experience of family caregivers of cancer patients with post-traumatic growth in Iran. Methods This qualitative study performed an inductive content analysis on 15 family caregivers selected through the purposive sampling method with maximum variation between April and August 2024 in Iran. Data were collected through face-to-face semi-structured in‑depth interviews. The processes of data collection and data analysis took place simultaneously. Latent Granheim and Lundman’s content analysis approach (2004) was used in this study. Results At the end of the data analysis, three categories (Surrender and Acceptance, Going Beyond Oneself, Finding Meaning and Purpose) and eight subcategories emerged. These findings represented the concept of post-traumatic growth. Conclusion Family caregivers of cancer patients, after accepting the disease, were striving for an appropriate compensatory response to this life-threatening disease. Therefore, this effort enabled them to look at all stages of life in the past until now with a different perspective. This perspective led to a new understanding of themselves, others, the disease, and ultimately, the meaning and purpose of worldly and after life, which is the same as post-traumatic growth and transcendence.